1998
DOI: 10.1021/la980269k
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Competitive Adsorption of Water and Methanoic Acid on Calcite and Fluorite Surfaces

Abstract: Atomistic simulation techniques were used to investigate the interaction between the minerals calcite and fluorite with water and methanoic acid. The relative adsorption energies suggest that methanoic acid preferentially adsorbs onto fluorite surfaces, while adsorption of water is energetically preferred over methanoic acid on the calcite cleavage plane in agreement with experiment. The coverage and configuration of adsorbed methanoic acid on the surfaces depends largely on lattice spacing between the cations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 49 publications
5
74
0
Order By: Relevance
“…The findings also conclude the wettability and dynamical properties, to be affected by confinement size of pores of reservoir rocks (Al-Quraishi and Khairy 2005;Cui et al 2003;Standnes and Austad 2000;Yuan et al 2015). A few investigations were also directed towards analysis of adsorption of organic molecules over clay (Hu et al 2014;Pernyeszi et al 1998;Wang et al 2013) (mainly kaolinite), as well as non-clay (Cooke et al 2010;de Leeuw and Parker 1998;Freeman et al 2009;Guiwu et al 2009;Keller et al 2015;Sakuma et al 2014) (mainly calcite) surfaces. In this regards, the main focus has been devoted to the {001} kaolinite or {1014} calcite structures, on the premise of holding the primary cleavage planes (Miller et al 2007;Sekkal and Zaoui 2013;Titiloye et al 1993;Zielke et al 2015).…”
Section: Introductionmentioning
confidence: 74%
“…The findings also conclude the wettability and dynamical properties, to be affected by confinement size of pores of reservoir rocks (Al-Quraishi and Khairy 2005;Cui et al 2003;Standnes and Austad 2000;Yuan et al 2015). A few investigations were also directed towards analysis of adsorption of organic molecules over clay (Hu et al 2014;Pernyeszi et al 1998;Wang et al 2013) (mainly kaolinite), as well as non-clay (Cooke et al 2010;de Leeuw and Parker 1998;Freeman et al 2009;Guiwu et al 2009;Keller et al 2015;Sakuma et al 2014) (mainly calcite) surfaces. In this regards, the main focus has been devoted to the {001} kaolinite or {1014} calcite structures, on the premise of holding the primary cleavage planes (Miller et al 2007;Sekkal and Zaoui 2013;Titiloye et al 1993;Zielke et al 2015).…”
Section: Introductionmentioning
confidence: 74%
“…Previous reports showed that oleic acid (OA) has a stronger collecting power for fluorite than for calcite [10][11][12]. In this work, SOA was used to improve its collecting power for calcite.…”
Section: Single Mineral Flotation Experiments Resultsmentioning
confidence: 99%
“…During optimization the top two layers of the surface cluster were relaxed with respect to energy and the bottom two layers were kept fixed. The stability of the mineral surface was determined by surface energy (γ ), which was calculated as per the method described by de Leeuw et al (40). The optimized reagent molecule was docked on this surface cluster and allowed to relax completely.…”
Section: Force Field Methodsmentioning
confidence: 99%
“…Several research groups are currently engaged in studying surfactant-surface interactions using molecular modeling tools (3,4,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). We present in this paper the results of molecular modeling of the interactions of alkyl hydroxamates with three calcium minerals and the correlations of these theoretically computed interaction energies with our own experimental microflotation results on the same system.…”
Section: Introductionmentioning
confidence: 99%